ANALISIS PENGARUHNYA PERCEIVED EASE OF USE, PERCEIVED USEFULNESS, DAN PERCEIVED BEHAVIORAL CONTROL TERHADAP AKTUALISASI PENGGUNAAN PADA MAHASISWA KOTA BATAM - Dessy Aliandrina; Dion Dewa Barata; Pulung Peranginangin (Program Sarjana Manajemen Universitas Internasional Batam, 2022)
The purpose of this study is to understand the influence of the variables Perceived Ease of Use, Perceived Usefulness, and Perceived Behavioral Control on the actualization of use in Batam city students. In this case, this study will investigate how the variables Perceived Ease of Use, Perceived Usefulness, and Perceived Behavioral Control can make users feel comfortable using an application, website or technology. The technique used by the author is a purposive sampling method, which is a sample used and selected through the knowledge of the researcher or according to the appropriate researcher to participate in this research. After the results of the respondents have been collected, the next author will test the data using PLS software. The results of the study explain that the variables Perceived Ease of Use, Perceived Usefulness, and Perceived Behavioral Control can create Intention to Use which affects users in using an application, website, or technology, so that an Actual to Use will be formed for users.